A Sustainable Approach of Toaster by Using Simplified Life Cycle Assessment: A Case Study - Ruqayah Ali Grmasha, Osamah J. Al-sareji (International Journal of Advanced Science and Technology, 2020)
Toaster is considered the main appliances in every household worldwide. Thus, it is necessary to analysis its life cycle and figures out which phase affects the environment and how its impacts could be alleviated. Simplified Life Cycle Assessment (SLCA) was conducted for the entire life cycle of Toaster considering raw materials phase, manufacturing phase, usage phase, End of life (EOL) and transportation. According to SLCA results, the Polypropylene scored the highest SLCA points (approximate 0.2117) among the materials used in the Toaster. This can be expected as it contributes to the major weight of Toaster. Copper scored the second-highest SLCA points (0.1318) because of its environmental impacts resulted from raw material extraction processes such as mining. This paper also pointed out that the hot spot analysis during the manufacturing phase has resulted from plastic injection moulding. In the life-cycle of Toaster, the obtained results of SCLA indicated that the usage phase had the highest SLCA points among all phases. This can result from the high consumption of electricity. After performing the sensitivity analysis, it is evidenced that replacing the conventional fossil fuel to renewable wind power would have a less environmental impact during the life-cycle of the Toaster.